Auditing and assurances services : an integrated approach - Arens, Alvin A.; Elder, Randal J.; Beasley, Mark S.; Hogan, Chris E. (Pearson, 2024)
"Auditing and Assurance Services examines the process of conducting an audit from start to finish. The text's primary objective is to illustrate auditing concepts using practical examples and real-world settings. Using key real audit decisions as their foundation, students will be able to successfully conduct an audit according to a financial reporting framework"--